A Bibliometric Study of Educational Marketing Strategy - Brillianty, Safira; Jabar, Cepi Safruddin Abdul (JURNAL AL-TANZIM, 2024)
Education marketing strategy is one of the management that schools must carry out to attract the interest of new students. This research aims to identify research developments related to the theme of educational marketing strategies. This research uses a qualitative approach with bibliometric techniques to investigate the general picture related to educational marketing strategy research. The data in this paper is taken from the Scopus database for 1981-2021, with the document type being articles. The analysis results show the dynamics of increasing and decreasing the number of educational marketing strategy studies. Bibliometric analysis in this study shows theme clusters that develop from the educational marketing strategy theme, the closeness of publication terms (co-occurrence), the most productive authors, and the publishing journals that produce the most educational marketing strategy themes. This research for Islamic education management implies that this research can be a reference for future researchers to study more on the theme of educational marketing strategies in Islamic educational institutions.